THE ROLE OF TIME MANAGEMENT FOR ADMINISTRATIVE ASSISTANTS IN IMPROVING ORGANIZATIONAL EFFICIENCY - Nangoy, Stanley (JIU (Jurnal Ilmiah Unklab), 2014)
Administrative assistants are expected to get the job done well and on time and are often required to take responsibility for tasks not directly associated with their function.  In addition, they are expected to assist their managers in managing their schedule and tasks as well as deal with a variety of questions and complaints from people within and outside of the organisation.  As managers mostly rely their administrative work on their administrative assistant, it is essential to ensure that the administrative assistants are well equipped to deal with ever-changing workloads and deadlines.  The only way for them to maintain control of their tasks and workload is to learn how to do more in less time and deal effectively with the constant interruptions in their working day.